Governing the wild : ecotours of power - Rutherford, Stephanie (University of Minnesota Press, 2011)
Take four emblematic American scenes: the Hall of Biodiversity at the American Museum of Natural History in New York; Disney's Animal Kingdom theme park in Orlando; an ecotour of Yellowstone and Grand Teton National Parks; the film An Inconvenient Truth. Other than expressing a common interest in the environment, they seem quite dissimilar. And yet, as Governing the Wild makes clear, these sites are all manifestations of green governmentality, each seeking to define and regulate our understanding, experience, and treatment of nature. Stephanie Rutherford shows how the museum presents a scientiz.